Urban geography : a global perspective - Pacione, Michael (London ; New York : Routledge, 2009)
Today, for the first time in the history of Humankind urban dwellers outnumber rural residents. Urban places, towns and cities, are of fundamental importance--for the distribution of population within countries; in the organisation of economic production, distribution and exchange; in the structuring of social reproduction and cultural life; and in the allocation and exercise of power. Furthermore, in the course of the present century the number of urban dwellers and level of global urbanisation are destined to increase. Even those living beyond the administrative or functional boundaries of a town or city will have their lifestyle influenced to some degree by a nearby, or even distant, city. The analysis of towns and cities is a central element of all social sciences including geography, which offers a particular perspective on and insight into the urban condition. The principal goal of this third edition of the book remains that of providing instructors and students of the contemporary city with a comprehensive introduction to the expanding field of urban studies. The structure of the first two editions is maintained, with minor amendments. Each of the thirty chapters has been revised to incorporate recent developments in the field. All of the popular study aids are retained; the glossary has been expanded; and chapter references and notes updated to reflect the latest research. This third edition also provides new and expanded discussions of key themes and debates including detailed consideration of metacities, boomburgs, public space, urban sprawl, balanced communities, urban economic restructuring, poverty and financial exclusion, the right to the city, urban policy, reverse migration, and traffic and transport problems.--Back cover.
-- Introduction -- PART ONE: THE STUDY OF URBAN GEOGRAPHY. 1. Urban geography: from global to local -- 2. Concepts and theory in urban geography -- PART TWO: AN URBANISING WORLD. 3. The origins and growth of cities -- 4. The global context of urbanisation and urban change -- 5. Regional perspectives on urbanisation and urban change -- 6. National urban systems -- PART THREE: URBAN STRUCTURE AND LAND USE IN THE WESTERN CITY. 7. Land use in the city -- 8. Urban planning and policy -- 9. New towns -- 10. Residential mobility and neighbourhood change -- 11. Housing problems and housing policy -- 12. Urban retailing -- 13. Urban transportation -- PART FOUR: LIVING IN THE CITY: ECONOMY, SOCIETY AND POLITICS IN THE WESTERN CITY. 14. The economy of cities -- 15. Poverty and deprivation in the Western city -- 16. National and local responses to urban economic change -- 17. Collective consumption and social justice in the city -- 18. Residential differentiation and communities in the city -- 19. Urban liveability -- 20. Power, politics and urban governance -- PART FIVE: URBAN GEOGRAPHY IN THE THIRD WORLD. 12. Third World urbanisation within a global urban system -- 22. Internal structure of Third World cities -- 23. Rural urban migration in the Third World -- 24. Urban economy and employment in the Third World -- 25. Housing the Third World urban poor -- 26. Environmental problems in Third World cities -- 27. Health in the Third World City -- 28. Traffic and transport in the Third World city -- 29. Poverty, power and politics in the Third World city -- PART SIX: PROSPECTIVE -- THE FUTURE OF THE CITY: CITIES OF THE FUTURE. 30. The future of the city -- cities of the future.
Includes bibliographical references (pages 627-669) and index.
Keywords: Urban geography